Suitability and limitations of native species for seed mixtures to re‐vegetate degraded areas. Issue 4 (20th February 2014) - Oliveira, Graça; Clemente, Adelaide; Nunes, Alice; Correia, Otília; Marrs, Rob
Abstract Questions How do native species perform when included in seed mixtures to re‐vegetate degraded areas? Is their germination and establishment affected by seeding density? Location Limestone quarry spoil, SW Portugal. Methods A glasshouse experiment simulating usual hydroseeding procedures (substrate, time of the year, slurry composition, seed mixture) was performed to evaluate the suitability of six native species (Origanum vulgare, Piptatherum miliaceum, Phagnalon saxatile, Sedum album, S. sediforme, Thymus mastichina) to re‐vegetate a Mediterranean quarry. Other native species were added to create the seed mixtures. Three treatments were assayed for each target species sown: (1) alone (T), (2) in a low‐density seed mixture (ca. 15 g·m−2), and (3) in a high‐density seed mixture (ca. 30 g·m−2). Plants were monitored for 8 months. Results The target species were able to germinate, establish and grow when sown alone, but their performance was drastically impaired when included in seed mixtures. This was related to plant morphologies, as some co‐seeded species rapidly developed large leaves, which presumably reduced resource availability for the small‐leaved seedlings of most target species. Almost no seedlings of the latter survived in the mixture treatments. Low‐ and high‐seeding densities yielded similar plant covers and heights. Conclusions Even when apparently suitable to restore a given site, candidate native species cannot simply be included in current re‐vegetation 'recipes', because their success largely depends on the density and seedling characteristics of the co‐seeded species (even if these are also native). The early performance and morphology of the latter must be taken into account in the design of seed mixtures used in restoration actions.